How Reliable are Commercially Available Glypican4 ELISA Kits? - Buhl, Joseph P.; Garten, Antje; Kratzsch, Jürgen; Kiess, Wieland; Penke, Melanie (Experimental and Clinical Endocrinology & Diabetes, 2020)
Objective Glypican4 is an interesting new adipokine, which seems to play an important role in developmental processes and is potentially associated with metabolic changes in obesity and type 2 diabetes mellitus. Currently, only a few studies examined glypican4 in human blood, mainly in adults.Design, Patients and Measurements The aim of our study was to investigate glypican4 serum levels in lean, overweight, and obese children and adolescents, to unravel a possible association between glypican4 serum levels and parameters of obesity and insulin resistance. In order to determine a suitable method for investigating glypican4 serum levels, we validated two commercially available human glypican4 ELISA kits, using serum and plasma samples of an obese, insulin-resistant patient, and a healthy control subject, a human recombinant glypican4 protein fragment and glypican4-overexpressing cell lysate.Results Using ELISA kit #1 we were not able to detect values above background level, apart from standard curve values. ELISA kit #2 initially seemed suitable to measure glypican4, but further validation experiments showed non-linearity of serial dilutions, no recognition of a human recombinant glypican4 protein fragment and non-linearity in the recovery of glypican4-overexpressing cell lysate. In addition, there was a considerable decrease (approx. 68%) of measured values between two experiments, performed at different time points with aliquots of the same serum sample. Contrary to that, further experiments found sample stability not to be compromised.Conclusions Extensive evaluation of the performance of two commercially available ELISA kits led to the conclusion that none of them is applicable for the measurement of glypican4 in human blood samples.
Keywords: adipocytokines; obesity; humans; insulin resistance; obesity; enzyme-linked immunosorbent assay; diabetes; autoimmunity